Transient structural distortion of metal-free Cu/Zn superoxide dismutase triggers aberrant oligomerization - Teilum, Kaare (National Academy of Sciences, 2009)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease linked to the misfolding of Cu/Zn superoxide dismutase (SOD1). ALS-related defects in SOD1 result in a gain of toxic function that coincides with aberrant oligomerization. The structural events triggering oligomerization have remained enigmatic, however, as is the case in other protein-misfolding diseases. Here, we target the critical conformational change that defines the earliest step toward aggregation. Using nuclear spin relaxation dispersion experiments, we identified a short-lived (0.4 ms) and weakly populated (0.7%) conformation of metal-depleted SOD1 that triggers aberrant oligomerization. This excited state emanates from the folded ground state and is suppressed by metal binding, but is present in both the disulfide-oxidized and disulfide-reduced forms of the protein. Our results pinpoint a perturbed region of the excited-state structure that forms intermolecular contacts in the earliest nonnative dimer/oligomer. The conformational transition that triggers oligomerization is a common feature of WT SOD1 and ALS-associated mutants that have widely different physicochemical properties. But compared with WT SOD1, the mutants have enhanced structural distortions in their excited states, and in some cases slightly higher excited-state populations and lower kinetic barriers, implying increased susceptibility to oligomerization. Our results provide a unified picture that highlights both (i) a common denominator among different SOD1 variants that may explain why diverse mutations cause the same disease, and (ii) a structural basis that may aid in understanding how different mutations affect disease propensity and progression.